Analysis Of The Influence Of The Inflation Rate, Interest Rates, And Minimum Wages In The District On Investment In Magelang District. - Yuda Shagy Rahmanda Putra; Syamsul Huda (Cita konsultindo, 2025)
This study aims to analyze the macroeconomic factors that influence investment in Magelang Regency. It uses quantitative time-series data from 2013 to 2023. The dependent variable is the value of realized investment in Magelang Regency, while the independent variables include inflation, interest rates, and the regency/city minimum wage (UMK).The analysis method used is multiple linear regression, preceded by classic assumption tests (normality,multicollinearity, heteroscedasticity,and autocorrelation) to ensure that the estimation model is unbiased (BLUE).The results show that the inflation variable affects investment, which is proven by a critical test value below 5%, at 0.0132. Meanwhile, the test results indicate that the interest rate variable does not have a significant effect on investment, as proven by a critical test value above 5%, at 0.5396. Finally, the research shows that the regency/city minimum wage variable affects investment, which is proven by a critical test value below 5%, at 0.026.